Pengaruh Gaya Kepemimpinan Dan Pengembangan Karir Terhadap Intensi Turnover: Kepuasan Kerja Sebagai Mediator - I Wayan Saklit (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This study aims to determine the Style of Leadership and Career Development effect on Turnover Intention in PT. Takenaka Indonesia, either directly or through job satisfaction as an intermediary factor. PT. Takenaka Indonesia is a Japanese company, which is engaged in construction services include design, supervision and contractor, established since 1994.The approach used in this study is a quantitative approach, whereas the method used to analyze the research data is The Structural Equation Modeling (SEM). The population in this study were employees of PT. Takenaka Indonesia, both permanent employees and contract employees who were three hundred and ninety-two,and the number of samples is one hundred and ninety-two, which taken using stratified random sampling technique. Based on Statistics test results using SEM analysis technique, it was found that (1) style of leadership and career development had a positive influence on job satisfaction; and (2) The style of leadership and career development a positive influence on turnover intention, either directly or through the Job Satisfaction